2002
DOI: 10.1017/s0021859602002678
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental variation for tocopherol content and composition in sunflower commercial hybrids

Abstract: Tocopherols are the most important compounds having antioxidant activity in sunflower seeds. The objective of the present research was to study the genetic and environmental variation for tocopherol content and composition in sunflower. Thirty-six sunflower hybrids were grown at 13 locations across all major areas of sunflower cultivation in southern Spain. Seed yield, 100 seed weight, oil content and tocopherol content and composition were determined. Tocopherol content ranged from 314·5 to 1024·5 mg/kg seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 8 publications
7
52
2
6
Order By: Relevance
“…This is in agreement with a previous study on sunflower commercial hybrids (Velasco et al, 2002). Genotype 3 location interaction did not influence the proportion of α-and β-tocopherol, for which the location and to a lesser extent the genotype effect were predominant.…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…This is in agreement with a previous study on sunflower commercial hybrids (Velasco et al, 2002). Genotype 3 location interaction did not influence the proportion of α-and β-tocopherol, for which the location and to a lesser extent the genotype effect were predominant.…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…Differences in agronomic traits were observed among all of the genotypes (Table S2). Variation in the contents of Toc and its isomers has been previously reported in oilseed crops (Dolde et al, 1999;Rocheford et al, 2002;Velasco et al, 2002). In our study, a significant amount of genotypic variation was observed in seed T-Toc, Toc isomers, and Toc composition.…”
Section: Variation In Toc Contents Of the Five Genotypessupporting
confidence: 77%
“…Data from Fernández-Moya et al, 2006;Ghazani and Marangoni, 2013;Gunstone, 2011;Marmesat et al, 2008;O'Brien, 2009; ND = Non Detectable; SO = Sunflower Oil; HOSO: High Oleic Sunflower Oil, MOSO = Mid Oleic Sunflower Oil; HSHOSO = High Stearic High Oleic Sunflower Oil; HPHOSO = High Palmitic High Oleic Sunflower Oil. Gotor et al, 2007Gotor et al, , 2014Gunstone, 2011;Marmesat et al, 2008;Velasco et al, 2002Velasco et al, , 2004; ND = Non Detectable; SO = Sunflower Oil; HOSO: High Oleic Sunflower Oil, MOSO = Mid Oleic Sunflower Oil; HPHOSO = High Palmitic High Oleic Sunflower Oil.…”
Section: Introductionmentioning
confidence: 99%